Teraźniejszość i przyszłość hungarologii, Poznań, 30.11‑01.12.2017 - Koutny, Ilona; Kornatowski, Paweł (Język. Komunikacja. Informacja, 2019)
Teraźniejszość i przyszłość hungarologii, Poznań, 30.11‑01.12.2017